UNMASKING CULTURE-NEGATIVE INFECTIONS: A SYSTEMATIC REVIEW AND HSROC META-ANALYSIS OF METAGENOMIC NEXT-GENERATION SEQUENCING (Asian Journal of Medical Research and Health Sciences, 2026)
Culture-negative infections represent a significant diagnostic challenge in clinical microbiology, often resulting in delayed diagnosis, inappropriate antimicrobial therapy, and increased morbidity and mortality. Conventional microbiological methods, including culture and targeted molecular assays, frequently fail to detect causative pathogens due to prior antibiotic exposure, fastidious organisms, intracellular pathogens, and low microbial burden. Metagenomic Next-Generation Sequencing (mNGS) has emerged as a transformative, culture-independent diagnostic modality capable of unbiased detection of a wide spectrum of pathogens, including bacteria, viruses, fungi, and parasites, directly from clinical specimens.This systematic review and hierarchical summary receiver operating characteristic (HSROC) meta-analysis aimed to evaluate the diagnostic accuracy and clinical utility of mNGS in identifying pathogens in culture-negative infections. A comprehensive literature search was conducted across PubMed, Scopus, Embase, and Web of Science for studies published between 2015 and 2025. Studies assessing mNGS in suspected infectious diseases with negative conventional cultures were included. Diagnostic accuracy parameters were extracted, and study quality was assessed using the QUADAS-2 tool. A bivariate random-effects model was employed to estimate pooled sensitivity and specificity, and HSROC curves were constructed.A total of 38 studies involving 4,562 patients were included. The pooled sensitivity and specificity of mNGS were 0.91 (95% CI: 0.87–0.94) and 0.86 (95% CI: 0.81–0.90), respectively. The diagnostic odds ratio was 68.4, indicating excellent discriminatory ability. Subgroup analyses demonstrated superior performance in central nervous system and bloodstream infections. mNGS influenced antimicrobial management in approximately 52% of cases. In conclusion, mNGS demonstrates high diagnostic accuracy and significant clinical utility in culture-negative infections. Its integration into routine clinical practice has the potential to enhance diagnostic precision and antimicrobial stewardship, although challenges related to cost, standardization, and data interpretation remain.